KONTRIBUSI TES PSIKOLOGIS TERHADAP SELF EFFICACY PENGAMBILAN KEPUTUSAN KARIR SISWA DI SEKOLAH BERBASIS PONDOK PESANTREN - Tentrem Basuki; Khayatun Nufus Akhsania; DYP Sugiharto; Muhammad Japar (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2020)
This study discusses psychology for students in Islamic boarding schools who have taken psychological tests and who have never taken a psychological test. The research method used is a comparison of research with data analysis of comparative test Career Decision Making Self-Efficacy Scale between students who have taken a psychological test and who have never received a psychological test at a boarding school. Bandura's Self-Efficacy Theory uses work theory, while the sample in this study uses cluster random sampling with a total of students (N = 22). Data collection was carried out through a direct survey consisting of 25 question items about self efficacy. The results of the t-test different test analysis showed no significant difference between students who had received a psychological test and who had never taken a psychological test in junior high school students in a boarding school based school. With the results of IQ tests (t (22) = 1,076, p> 0.05), aptitude tests (t (22) = 1,731, p> 0.05) and, interest tests (t (22) = 1,137, p> 0 , 05). These results indicate that there is no significant difference between students who take psychological tests who take IQ, aptitude, and interest tests, and who have never taken a psychological test, one of the contributing factors is representing irregular beliefs or relationships with what is on almighty will in providing sustenance, as long as his servant wants to succeed.